2009
DOI: 10.1134/s1068162009010026
|View full text |Cite
|
Sign up to set email alerts
|

New weak toxins from the cobra venom

Abstract: A protein with M 7485 Da containing five disulfide bonds was isolated from the venom of cobra Naja oxiana using various types of liquid chromatography. The complete amino acid sequence of the protein was determined by protein chemistry methods, which permitted us to assign it to the group of weak toxins. This is the first weak toxin isolated from the venom of N. oxiana. In a similar way, two new toxins with M 7628 and 7559 Da, which fall into the range of weak toxin masses, were isolated from the venom of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Potent α-neurotoxicity preceded the evolution of the high-pressure front-fanged system of elapids, as was revealed by our discovery of α-colubritoxin, the first 3FTx isolated and characterized from a non-front-fanged lineage [59]. The toxin was of the same form as had been studied in elapid snakes previously, where they had been called ‘weak neurotoxins’ since they were only weakly potent on mice [137,138,139,140,141,142,143,144,145,146,147,148,149]. A problem that had also confounded studies of Boiga irregularis (brown tree snake), which had thus concluded they were non-venomous based on their effects in a murine model [150,151,152,153,154,155].…”
Section: Resultsmentioning
confidence: 99%
“…Potent α-neurotoxicity preceded the evolution of the high-pressure front-fanged system of elapids, as was revealed by our discovery of α-colubritoxin, the first 3FTx isolated and characterized from a non-front-fanged lineage [59]. The toxin was of the same form as had been studied in elapid snakes previously, where they had been called ‘weak neurotoxins’ since they were only weakly potent on mice [137,138,139,140,141,142,143,144,145,146,147,148,149]. A problem that had also confounded studies of Boiga irregularis (brown tree snake), which had thus concluded they were non-venomous based on their effects in a murine model [150,151,152,153,154,155].…”
Section: Resultsmentioning
confidence: 99%
“…WTX, ␣-Ctx, and NT II were obtained as described previously (23)(24)(25) and OWT as described previously (26). NT I was obtained as described previously (27) with additional purification by reversed phase HPLC.…”
Section: Methodsmentioning
confidence: 99%
“…This toxin was considered a novel long chain 3FTx, because of its reversible antagonistic effect on muscle-type and weaker but also on neuronal α7 nAChR. In other similar toxins, the activity is commonly almost or totally irreversible [ 56 ]. As in the subgroup 2-A, sequences from subgroup 2-B are differentiated by the presence of a fifth extra disulfide bridge located in the finger I, as found in Candoxin.…”
Section: Discussionmentioning
confidence: 99%